The Use of Same-Day Hearing Aid Fitting with Telehealth Follow-up Care: A Case Study of a Veteran Presenting with Tinnitus and Auditory Processing Disorder Symptoms - Jedlicka, David P. (Seminars in Hearing, 2021)
Providing same-day hearing aid fitting appointments to patients being seen in an audiology clinic for an audiometric evaluation may help decrease clinic wait times and reduce the need for future in-person appointments. Prior to 2020, the Veterans Administration (VA) Healthcare System did not allow hearing aid manufacturers to provide functional demonstration (demo) hearing aids to VA audiology clinics. Due to the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2/COVID-19) pandemic, this rule was changed to minimize the number of required in-person VA audiology appointments. The audiology clinic at the Pittsburgh VA Healthcare System developed a hearing aid fitting protocol using demo hearing aids to provide same-day hearing aid fitting appointments. This case study pertains to a female Veteran who presented to the clinic with complaints of decreased hearing and bothersome tinnitus. The patient completed a comprehensive audiometric evaluation, auditory processing disorder screening, hearing aid evaluation, and hearing aid fitting in the clinic. All follow-up appointments were scheduled to be completed via telehealth. The initial findings in this case study indicate that same-day hearing aid fittings can be successful for some patients. Future telehealth follow-up appointments will determine this patient's level of success using hearing aid–related outcome measures.
Keywords: hearing aids; self-perceived hearing handicap; mild hearing loss; remote programming; auditory processing disorder; tinnitus